Antibiotic Utilization in Pediatric Hospitalized Patients – A Single Center Study - Bytyqi, Hasime Qorraj; Hoxha, Rexhep; Bahtiri, Elton; Krasniqi, Valon; Krasniqi, Shaip (Open access Macedonian journal of medical sciences, 2017)
BACKGROUND: Antibiotics are among the most commonly prescribed drugs in paediatrics. In most cases, antibiotics are started on an empirical basis, without proof of a bacterial infection, either before the start of therapy or afterwards.AIM: The main objective of this study was to analyse the consumption of antibiotics in hospitalised paediatric patients.MATERIAL AND METHODS: This retrospective study investigated the consumption of antimicrobials in defined daily doses (DDDs according to the Anatomical Therapeutical Chemical/DDD index) in Pulmonology, Gastroenterology and Nephrology Departments at Pediatric Clinic of the tertiary hospital. The data on the consumption of antimicrobials were collected for five years by using properly designed form. The consumption was related to days of hospital care.RESULTS: The most utilised antibiotics group in all three departments Pulmonology, Gastroenterology and Nephrology Departments were penicillins. Cephalosporins were mostly used in Pulmonology department. Metronidazole and Chloramphenicol were used in minimal quantities in all three departments.CONCLUSION: This study demonstrates that surveillance programs on antibiotic resistance should be established and accompanied by analyses of drug utilisation data which can aid in the creation of valid cross-national studies on antibiotic usage and resistance, to motivate improvements in prescribing and guideline-directed antibiotic prescribing.